Respuesta :

1:

y = 2x

x + y = 6

3x = 6

x= 2

y = 4

2:

y = 2x - 5

x + y = 4

x + 2x - 5 = 4

x + 2x = 9

3x = 9

x = 3

y = 1

3:

x + y = 7

2x - y = 5

x = 7 - y

2x = 14 - 2y

14 - 2y - y = 5

- 9 = - 3y

3y = 9

y = 3

x = 4

4:

x + 9y = - 6

2x - 9y = 15

9y = 2x - 15

x + 2x - 15 = - 6

3x = 9

x = 3

y = - 1

5:

x + 2y = 4

y = 2x + 7

2y = 4x + 14

x + 4x + 14 = 4

5x = - 10

x = - 2

y = 3

6:

x - 4y = 16

y = 1 - x

4y = 4 - 4x

x - 4 + 4x = 16

5x = 20

x = 4

y = -3

7:

4x - y = 10

x + y = 5

y = 4x - 10

x + 4x - 10 = 5

5x = 15

x=3

y = 2

8:

2x + y = 10

3x = y

y = 10 - 2x

10 - 2x = 3x

10 = 5x

x = 2

y = 6

9:

-5x - y = 20

y = 3x

y = - 5x - 20

-5x - 20 = 3x

8x = - 20

2x = - 5

x = - 2.5

y = - 7.5

10:

2x - y = -1

x = 17 - 3y

y = 2x + 1

3y = 6x + 3

17 - 6x - 3 = x

14 = 7x

x = 2

y = 3

11:

3x + y = 3

y = 2x - 7

y = 3 - 3x

3 - 3x = 2x - 7

10 = 5x

x = 2

y = - 3

12:

2x + 3y = 17

3x - 2y = - 0.5

2y = 3x + .5

y = 1.5x + .25

3y = 4.5x + .75

2x + 4.5x + .75 = 17

16.25 = 6.5x

16.25 / 6.5 = x

x = 2.5

y = 4

13:

x - 2y = 5

3x + 2y = 23

3x = 15 + 6y

15 + 6y + 2y = 23

8 = 8y

x = 7

y = 1

14:

2x = 5y + 8

3x + 2y = 31

x = 2.5y + 4

3x = 7.5y + 12

7.5y + 12 + 2y = 31

9.5y = 19

y = 19 / 9.5

x = 9

y = 2

took a lot of time so please give brainliest

ACCESS MORE